Method for extracting lithium from clay lithium ore
By using carbon source and foaming agent to prepare aerogels during the lithium extraction process of clay lithium ore, and calcining treatment under microwave roasting conditions, the problem of sintering phenomenon and high impurity leaching rate is solved, and the effect of efficient lithium extraction is achieved.
Patent Information
- Application Number
- CN202411881642.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is prone to sintering in the process of extracting lithium from clay lithium ore, which makes it difficult to remove the sample, and the leaching rate of impurities such as aluminum and iron is high, affecting the separation and purification of lithium.
By mixing the carbon source and the foaming agent for heat treatment, a solvent is prepared and acid-treated with clay lithium ore to form an aerogel-like manner. Then the calcination treatment is carried out under microwave calcination conditions, replacing the traditional heating method, decomposing the salt and increasing the leaching rate of lithium.
The sintering phenomenon is effectively avoided, the leaching rate of aluminum and iron is reduced, and the leaching rate of lithium is increased, and the sample is heated more uniformly.
Smart Images

Figure CN119824245A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium extraction from lithium ore, and in particular to a method for extracting lithium from clay lithium ore. Background Art
[0002] As an important energy strategic metal, lithium is currently widely used in new energy, nuclear energy, medical and ceramic fields, and is known as "white oil". Based on the importance of lithium, the development of lithium will also attract much attention in the future. At present, lithium resources can be divided into three types: one is hard rock type, such as spodumene, lepidolite, petalite and pyroxenite; one is salt lake brine lithium resources; and the last one is clay-type lithium ore. The lithium resources currently developed and utilized are mainly hard rock type and salt lake brine type lithium resources. However, with the continuous increase in demand for lithium resources, the development and utilization of clay-type lithium resources will inevitably attract much attention.
[0003] The main methods for extracting lithium from clay lithium ore include sulfate roasting, sulfuric acid roasting and chlorination roasting. Among them, the sulfate roasting method faces the problems of high roasting temperature and complex leachate composition, resulting in high energy consumption and difficulty in impurity removal. The chlorination roasting method faces the problems of high roasting temperature, equipment corrosion and exhaust gas pollution.
[0004] In contrast, the sulfuric acid roasting method can effectively extract lithium from clay lithium ore under relatively mild and simple conditions. The prior art provides a method for efficiently leaching lithium from lithium-containing clay ore, which crushes the clay lithium ore and grinds it in a rod mill, filters it, dries it and breaks it up, then mixes it with concentrated sulfuric acid in a certain proportion, puts it in a muffle furnace and keeps it warm for a period of time (keep it warm for 1 to 4 hours at 150 to 210 ° C), cools it to room temperature, takes out the sample, grinds it evenly and leaches it with water, and separates the solid and liquid to obtain a lithium-containing leachate. Although this method can effectively leach lithium at a lower temperature, a large amount of impurities such as aluminum, iron, magnesium and potassium are also leached in large quantities, resulting in the loss of lithium in the form of lithium aluminum hydroxide during the subsequent purification process, which brings difficulties to the subsequent separation and purification of lithium. In addition, sintering is prone to occur during the insulation process, which makes it difficult to remove the sample from the crucible, thereby increasing the difficulty of subsequent leaching operations. In addition, there is a method of mixing sulfuric acid with lithium aluminum silicate minerals and then roasting them in two stages in a muffle furnace to convert aluminum sulfate and iron sulfate into aluminum oxide and iron oxide, and selective extraction of lithium is achieved after water leaching. However, in this traditional heating method, heat is transferred from the surface to the inside of the sample, resulting in uneven temperature distribution in the sample, resulting in local overheating, and then leading to the formation of insoluble LiAlSiO4 and LiAlO2, which reduces the leaching of lithium to a certain extent. Therefore, it is urgent to provide a method for extracting lithium from clay lithium ore, which can avoid sintering during the insulation process, reduce the leaching rate of aluminum and iron, and effectively improve the leaching rate of lithium. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a method for extracting lithium from clay lithium ore, which can improve the sintering phenomenon in the existing sulfuric acid roasting process and extract lithium efficiently and selectively.
[0006] To this end, the present invention provides a method for extracting lithium from clay lithium ore, the method comprising:
[0007] The carbon source and the foaming agent are mixed and heat-treated to obtain a solvent;
[0008] Treating the clay lithium ore with acid to obtain a first mixture;
[0009] mixing the first mixture and the solvent to obtain a second mixture;
[0010] calcining the second mixture to obtain an aerogel-like substance;
[0011] The aerogel-like substance is subjected to microwave calcination to obtain a third mixture;
[0012] The third mixture is subjected to water leaching treatment to obtain a leaching solution and leaching residue.
[0013] In the traditional sulfation roasting process, sintering phenomenon is prone to occur during the heat preservation process, which makes it difficult to remove the sample from the crucible, thereby increasing the difficulty of subsequent leaching operations. In contrast, the present invention uses carbon source and foaming agent as raw materials to obtain aerogel-like, which has a fluffy and porous structure, can significantly reduce the sintering phenomenon of clay lithium ore during acidification roasting, reduce the difficulty of operation, and does not affect the conversion of valuable elements in clay lithium ore into salt. In the preparation process of aerogel-like, the carbon source decomposes to produce charcoal, and the porous structure of charcoal and aerogel-like is conducive to the efficient absorption of microwaves and promotes the efficient decomposition of subsequent salts. Afterwards, the aerogel-like is subjected to microwave roasting treatment instead of the traditional heating method (heat is transferred from the sample surface to the inside) to carry out the salt decomposition process, avoiding the problems such as uneven heating of materials caused by conventional heating, causing higher temperatures in certain areas of the material, causing melting and adhesion of the material, reducing the specific surface area of the material, and reducing the lithium leaching rate. At the same time, the porous structure and high degree of graphitization of aerogels can significantly improve their dielectric properties and microwave absorption capacity. The improvement of microwave absorption capacity can make the salt decomposition efficiency higher, the sample is heated more evenly, and local overheating will not occur, thereby increasing the lithium leaching rate.
[0014] According to an embodiment of the present invention, the carbon source includes at least one of glucose, sucrose, maltose, fructose and lactose.
[0015] According to an embodiment of the present invention, the foaming agent includes at least one of urea, ammonium chloride, melamine, magnesium nitrate, dicyandiamide, and hexamethylenetetramine.
[0016] According to an embodiment of the present invention, the mass ratio of the carbon source to the foaming agent is 1:(0.5-1.5).
[0017] According to an embodiment of the present invention, the temperature of the heat treatment is 100-130°C.
[0018] According to an embodiment of the present invention, the heat treatment time is 8 to 12 minutes.
[0019] According to an embodiment of the present invention, the acid treatment comprises mixing the clay lithium ore with sulfuric acid.
[0020] According to an embodiment of the present invention, the concentration of the sulfuric acid is 70-90 wt %.
[0021] According to an embodiment of the present invention, the mass ratio of sulfuric acid to clay lithium ore is (1-3):1.
[0022] According to an embodiment of the present invention, the mass ratio of the solvent to the first mixture is 1:(1-4).
[0023] According to an embodiment of the present invention, the temperature of the calcination treatment is 200-300°C.
[0024] According to an embodiment of the present invention, the calcination treatment time is 0.5 to 3 hours.
[0025] According to an embodiment of the present invention, the calcination process is performed in an inert atmosphere.
[0026] According to an embodiment of the present invention, the power of the microwave roasting process is 0.1-6 kW.
[0027] According to an embodiment of the present invention, the temperature of the microwave roasting treatment is 600-800°C.
[0028] According to an embodiment of the present invention, the microwave roasting treatment is performed for 0.5 to 2.5 hours.
[0029] According to an embodiment of the present invention, the temperature of the water immersion treatment is 60-100°C.
[0030] According to an embodiment of the present invention, the water immersion treatment time is 60 to 150 minutes.
[0031] According to an embodiment of the present invention, the method further comprises: subjecting the leaching solution to lithium precipitation treatment to obtain lithium carbonate.
[0032] According to an embodiment of the present invention, the particle size of the clay lithium ore is 80-325 meshes.
[0033] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0035] Figure 1 The flowchart of the method for extracting lithium from clay lithium ore provided by the present invention is shown. DETAILED DESCRIPTION
[0036] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0037] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0038] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0039] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0040] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0041] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0042] According to an embodiment of the present invention, the present invention provides a method for extracting lithium from clay lithium ore, see Figure 1 The flowchart shown specifically includes the following steps:
[0043] (1) A carbon source and a foaming agent are mixed and heat treated to obtain a solvent.
[0044] According to a specific embodiment of the present invention, the types of the carbon source and the foaming agent are not particularly limited, and those skilled in the art can select them according to the circumstances. As some specific examples, the carbon source includes but is not limited to glucose, sucrose, maltose, fructose, and lactose; the foaming agent includes but is not limited to urea, ammonium chloride, melamine, magnesium nitrate, dicyandiamide, and hexamethylenetetramine.
[0045] According to a specific embodiment of the present invention, the mass ratio of the carbon source to the foaming agent is 1:(0.5-1.5), such as 1:0.5, 1:0.75, 1:1, 1:1.25, 1:1.5, etc. When the carbon source is too little, it will affect the formation of the graphitized skeleton, reduce the conductivity of the aerogel-like material, and further affect the subsequent microwave roasting effect; when the foaming agent is too little, it will affect the subsequent bubbling process, reduce the number of pores and specific surface area of the aerogel-like material, and further affect the microwave absorption efficiency of the acidification roasting process and the salt decomposition process. When the mass ratio of the carbon source to the foaming agent is 1:(0.5-1.5), the sintering effect of the acidification process can be suppressed and the microwave absorption efficiency of the salt decomposition process can be increased.
[0046] According to a specific embodiment of the present invention, the temperature and time of the heat treatment are not particularly limited, as long as a clear and transparent liquid solvent is formed. As some specific examples, the temperature of the heat treatment is 100-130°C, for example, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, etc.; the time of the heat treatment is 8-12min, for example, 8min, 9min, 10min, 11min, 12min, etc.
[0047] According to a specific embodiment of the present invention, this step further comprises mixing the carbon source and the foaming agent, grinding them to obtain a powdery mixture, and heat-treating the powdery mixture to obtain a solvent.
[0048] (2) Treating the clay lithium ore with acid to obtain a first mixture.
[0049] This step can convert the valuable metals in the clay lithium ore into salts. According to a specific embodiment of the present invention, the acid used in the acid treatment is not particularly limited, and is preferably sulfuric acid, to achieve the conversion of the valuable metals in the clay lithium ore into sulfates (such as iron sulfate, aluminum sulfate, etc.).
[0050] According to a specific embodiment of the present invention, the concentration of the sulfuric acid is 70-90wt%. As some specific examples, the concentration of the sulfuric acid can be 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, etc., which can be obtained by mixing concentrated sulfuric acid and water to obtain sulfuric acid of the target concentration.
[0051] According to a specific embodiment of the present invention, the mass ratio of sulfuric acid to clay lithium ore is (1-3):1. As some specific examples, the mass ratio of sulfuric acid to clay lithium ore is 1:1, 2:1, 3:1, etc.
[0052] According to a specific embodiment of the present invention, the particle size of the clay lithium ore is 80-325 mesh. As some specific examples, the particle size of the clay lithium ore can be 80 mesh, 100 mesh, 150 mesh, 200 mesh, 250 mesh, 300 mesh, 325 mesh, etc., which can be achieved by crushing, ball milling, etc.
[0053] (3) Mixing the first mixture and the solvent to obtain a second mixture.
[0054] According to a specific embodiment of the present invention, the mass ratio of the solvent to the first mixture is 1: (1-4), such as 1: 1, 1: 2, 1: 3, 1: 4, etc., thereby ensuring that the aerogel obtained subsequently has a porous structure and inhibiting the sintering and agglomeration phenomenon caused by excessive water when the sulfuric acid solution reacts with the clay lithium ore. If the amount of the solvent added is too small, due to the compatibility problem between the solvent and the clay lithium ore, the solvent cannot completely wrap the clay lithium ore, resulting in leakage of the clay lithium ore, and the leaked clay lithium ore sintering occurs during the roasting process, the sintered product has a large particle size, and the lithium leaching rate is reduced during leaching; if the amount of the solvent added is too much, the contribution to the lithium leaching rate is not obvious, but the preparation cost is increased.
[0055] (4) calcining the second mixture to obtain an aerogel-like substance.
[0056] The roasting process can achieve full contact between the clay lithium ore and the acid solution. During the roasting process, the foaming agent will decompose to produce gas, and the carbon source will be heated to make the solvent viscous, wrapping the bubbles, and finally obtaining an aerogel-like structure. This structure is fluffy and porous, which can significantly reduce the sintering phenomenon of the clay lithium ore during the acidification roasting process, reduce the difficulty of operation, and do not affect the conversion of valuable elements in the clay lithium ore into salt. In addition, the carbon source decomposes into carbon in this process, which can improve the electromagnetic wave absorption capacity, thereby improving the efficiency of subsequent microwave roasting.
[0057] According to a specific embodiment of the present invention, the temperature and time of the calcination treatment are not particularly limited. As some specific examples, the temperature of the calcination treatment is 200-300°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, etc.; the time of the calcination treatment is 0.5-3h, for example, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, etc.
[0058] According to a specific embodiment of the present invention, the calcination is performed in an inert atmosphere, and the carbon source will decompose into char and water vapor under oxygen-free conditions, which is helpful to form a porous aerogel-like substance. The inert atmosphere includes but is not limited to nitrogen.
[0059] (5) Subjecting the aerogel to microwave calcination to obtain a third mixture.
[0060] This step uses microwave roasting to replace the traditional heating method (heat is transferred from the sample surface to the inside) to decompose the salt (obtained by the aforementioned acid treatment), that is, the aerogel-like structure obtained by acid roasting is placed in a microwave roasting device for roasting, so that the salt (such as aluminum sulfate, iron sulfate, etc.) is decomposed into their respective oxides. The porous structure and high degree of graphitization of the aerogel-like structure can significantly improve its dielectric properties and microwave absorption capacity. The improvement of microwave absorption capacity can make the salt decomposition efficiency higher, the sample is heated more evenly, and no local overheating occurs, thereby increasing the lithium leaching rate.
[0061] According to a specific embodiment of the present invention, the power, temperature and time of the microwave roasting treatment are not particularly limited. As some specific examples, the power of the microwave roasting treatment is 0.1-6kW, for example, 0.1kW, 1kW, 2kW, 3kW, 4kW, 5kW, 6kW, etc.; the temperature of the microwave roasting treatment is 600-800°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, etc.; the time of the microwave roasting treatment is 0.5-2.5h, for example, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, etc.
[0062] (6) subjecting the third mixture to water leaching to obtain a leaching solution and leaching residue.
[0063] According to a specific embodiment of the present invention, the temperature and time of the water immersion treatment are not particularly limited. As some specific examples, the temperature of the water immersion treatment is 60-100°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.; the time of the water immersion treatment is 60-150min, for example, 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, etc.
[0064] According to a specific embodiment of the present invention, the liquid-to-solid ratio in the water immersion treatment is not particularly limited. As some specific examples, the liquid-to-solid ratio in the water immersion treatment is 2 to 5 mL / g, such as 2 mL / g, 2.5 mL / g, 3 mL / g, 3.5 mL / g, 4 mL / g, 4.5 mL / g, 5 mL / g, etc.
[0065] According to a specific embodiment of the present invention, this step further includes: subjecting the leachate to lithium precipitation treatment to obtain lithium carbonate. The lithium precipitation treatment is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, a compound that can convert lithium into a precipitated form, such as sodium carbonate, can be added to the leachate.
[0066] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0067] The main components of the clay lithium ore used in the present invention are shown in Table 1.
[0068] Table 1
[0069] element <![CDATA[Li2O / %]]> <![CDATA[Al2O3 / %]]> <![CDATA[K2O / %]]> <![CDATA[Na2O / %]]> <![CDATA[Fe2O3 / %]]> CaO / % MgO / % <![CDATA[TiO2 / %]]> <![CDATA[SiO2 / %]]> content 0.595 40.011 4.521 0.936 1.756 0.087 10.62 1.141 18.032
[0070] Example 1
[0071] This embodiment provides a method for extracting lithium from clay lithium ore:
[0072] S1: Clay-type lithium ore is crushed and ball-milled to 200 mesh to obtain clay lithium ore powder;
[0073] S2: 50 g of clay lithium ore powder and 80 wt % of sulfuric acid are fully mixed at a mass ratio of 1.8:1 to obtain a first mixture;
[0074] S3: Glucose and urea are ground in a mass ratio of 1:1, and the temperature is raised to 120° C. in an oven under atmospheric conditions to form a clear and transparent liquid solvent after about 10 minutes;
[0075] S4: the solvent obtained in step S3 is fully mixed with the first mixture at a mass ratio of 1:3 to obtain a second mixture, the second mixture is placed in a tubular furnace, and calcined under nitrogen protection at a temperature of 300° C. for 2 h, and an aerogel-like substance is formed after the calcination;
[0076] S5: placing the aerogel into a corundum crucible, and introducing a microwave heating device for efficient calcination, wherein the frequency of the microwave calcination is set to 2.45 GHz, the power is set to 2 kW, the microwave calcination temperature is set to 700° C., and the calcination time is 2 h. After the calcination, the decomposition of iron sulfate and aluminum sulfate is completed to obtain a third mixture;
[0077] S6: Grind the third mixture with a ball mill, and conduct a leaching experiment with pure water. The leaching temperature is 80° C., the leaching time is 2 h, and the liquid-to-solid ratio is 3 mL / g. After the leaching is completed, the leaching rates of iron, aluminum, and lithium are calculated.
[0078] Example 2
[0079] This embodiment provides a method for extracting lithium from clay lithium ore:
[0080] S1: Clay-type lithium ore is crushed and ball-milled to 200 mesh to obtain clay lithium ore powder;
[0081] S2: 50 g of clay lithium ore powder and 80 wt % of sulfuric acid are fully mixed at a mass ratio of 1.8:1 to obtain a first mixture;
[0082] S3: Glucose and urea are ground in a mass ratio of 1:1.5, and the temperature is raised to 120° C. in an oven under atmospheric conditions to form a clear and transparent liquid solvent after about 10 minutes;
[0083] S4: the solvent obtained in step S3 is fully mixed with the first mixture at a mass ratio of 1:3 to obtain a second mixture, the second mixture is placed in a tubular furnace, and calcined under nitrogen protection at a temperature of 300° C. for 2 h, and an aerogel-like substance is formed after the calcination;
[0084] S5: placing the aerogel into a corundum crucible, and introducing a microwave heating device for efficient calcination, wherein the frequency of the microwave calcination is set to 2.45 GHz, the power is set to 2 kW, the microwave calcination temperature is set to 700° C., and the calcination time is 2 h. After the calcination, the decomposition of iron sulfate and aluminum sulfate is completed to obtain a third mixture;
[0085] S6: Grind the third mixture with a ball mill, and conduct a leaching experiment with pure water. The leaching temperature is 80° C., the leaching time is 2 h, and the liquid-to-solid ratio is 3 mL / g. After the leaching is completed, the leaching rates of iron, aluminum, and lithium are calculated.
[0086] Example 3
[0087] This embodiment provides a method for extracting lithium from clay lithium ore:
[0088] S1: Clay-type lithium ore is crushed and ball-milled to 200 mesh to obtain clay lithium ore powder;
[0089] S2: 50 g of clay lithium ore powder and 80 wt % of sulfuric acid are fully mixed at a mass ratio of 1.8:1 to obtain a first mixture;
[0090] S3: Glucose and urea are ground in a mass ratio of 1:1.25, and the temperature is raised to 120° C. in an oven under atmospheric conditions to form a clear and transparent liquid solvent after about 10 minutes;
[0091] S4: the solvent obtained in step S3 is fully mixed with the first mixture at a mass ratio of 1:3 to obtain a second mixture, the second mixture is placed in a tubular furnace, and calcined under nitrogen protection at a temperature of 300° C. for 2 h, and an aerogel-like substance is formed after the calcination;
[0092] S5: placing the aerogel into a corundum crucible, and introducing a microwave heating device for efficient calcination, wherein the frequency of the microwave calcination is set to 2.45 GHz, the power is set to 2 kW, the microwave calcination temperature is set to 700° C., and the calcination time is 2 h. After the calcination, the decomposition of iron sulfate and aluminum sulfate is completed to obtain a third mixture;
[0093] S6: Grind the third mixture with a ball mill, and conduct a leaching experiment with pure water. The leaching temperature is 80° C., the leaching time is 2 h, and the liquid-to-solid ratio is 3 mL / g. After the leaching is completed, the leaching rates of iron, aluminum, and lithium are calculated.
[0094] Comparative Example 1
[0095] This embodiment provides a method for extracting lithium from clay lithium ore:
[0096] S1: Clay-type lithium ore is crushed and ball-milled to 200 mesh to obtain clay lithium ore powder;
[0097] S2: 50 g of clay lithium ore powder and 80 wt % of sulfuric acid are fully mixed at a mass ratio of 1.8:1 to obtain a first mixture;
[0098] S3: Glucose and urea are ground in a mass ratio of 1:1.25, and the temperature is raised to 120° C. in an oven under atmospheric conditions to form a clear and transparent liquid solvent after about 10 minutes;
[0099] S4: the solvent obtained in step S3 is fully mixed with the first mixture at a mass ratio of 1:5 to obtain a second mixture, the second mixture is placed in a tubular furnace, and calcined under nitrogen protection at a temperature of 300° C. for 2 h, and an aerogel-like substance is formed after the calcination;
[0100] S5: placing the aerogel into a corundum crucible, and introducing a microwave heating device for efficient calcination, wherein the frequency of the microwave calcination is set to 2.45 GHz, the power is set to 2 kW, the microwave calcination temperature is set to 700° C., and the calcination time is 2 h. After the calcination, the decomposition of iron sulfate and aluminum sulfate is completed to obtain a third mixture;
[0101] S6: Grind the third mixture with a ball mill, and conduct a leaching experiment with pure water. The leaching temperature is 80° C., the leaching time is 2 h, and the liquid-to-solid ratio is 3 mL / g. After the leaching is completed, the leaching rates of iron, aluminum, and lithium are calculated.
[0102] Comparative Example 2
[0103] This comparative example provides a method for extracting lithium from clay lithium ore:
[0104] S1: Clay-type lithium ore is crushed and ball-milled to 200 mesh to obtain clay lithium ore powder;
[0105] S2: 50 g of clay lithium ore powder and 80 wt % of sulfuric acid were fully mixed at a mass ratio of 1.8:1 to obtain a mixture;
[0106] S3: placing the mixture into a tube furnace, heating it to 300°C and calcining it for 2h;
[0107] S4: Use water to leach the roasted sample at a leaching temperature of 80°C, a leaching time of 2h, and a leaching liquid-to-solid ratio of 3mL / g. After the leaching is completed, the leaching rates of iron, aluminum, and lithium are calculated.
[0108] Comparative Example 3
[0109] This comparative example provides a method for extracting lithium from clay lithium ore:
[0110] S1: Clay-type lithium ore is crushed and ball-milled to 200 mesh to obtain clay lithium ore powder;
[0111] S2: 50 g of clay lithium ore powder and 80 wt % of sulfuric acid are fully mixed at a mass ratio of 1.8:1 to obtain a first mixture;
[0112] S3: Glucose and the first mixture are fully mixed in a mass ratio of 1:3 to obtain a second mixture, the second mixture is placed in a tubular furnace, and then roasted under nitrogen protection at a temperature of 300° C. for 2 h. After the roasting, the sintering phenomenon of the sample is observed;
[0113] S4: Use water to leach the roasted sample at a leaching temperature of 80°C, a leaching time of 2h, and a leaching liquid-to-solid ratio of 3mL / g. After the leaching is completed, the leaching rates of iron, aluminum, and lithium are calculated.
[0114] Comparative Example 4
[0115] This comparative example provides a method for extracting lithium from clay lithium ore:
[0116] S1: Clay-type lithium ore is crushed and ball-milled to 200 mesh to obtain clay lithium ore powder;
[0117] S2: 50 g of clay lithium ore powder and 80 wt % of sulfuric acid are fully mixed at a mass ratio of 1.8:1 to obtain a first mixture;
[0118] S3: urea and the first mixture are fully mixed in a mass ratio of 1:3 to obtain a second mixture, the second mixture is placed in a tubular furnace, and then calcined under nitrogen protection at a temperature of 300° C. for 2 h. After the calcination, the sintering phenomenon of the sample is observed;
[0119] S4: Use water to leach the roasted sample at a leaching temperature of 80°C, a leaching time of 2h, and a leaching liquid-to-solid ratio of 3mL / g. After the leaching is completed, the leaching rates of iron, aluminum, and lithium are calculated.
[0120] Comparative Example 5
[0121] This comparative example provides a method for extracting lithium from clay lithium ore:
[0122] S1: Clay-type lithium ore is crushed and ball-milled to 200 mesh to obtain clay lithium ore powder;
[0123] S2: 50 g of clay lithium ore powder and 80 wt % of sulfuric acid are fully mixed at a mass ratio of 1.8:1 to obtain a first mixture;
[0124] S3: Glucose and urea are ground in a mass ratio of 1:0.25, and the temperature is raised to 120° C. in an oven under atmospheric conditions to form a clear and transparent liquid solvent after about 10 minutes;
[0125] S4: the solvent obtained in step S3 is fully mixed with the first mixture at a mass ratio of 1:3 to obtain a second mixture, the second mixture is placed in a tubular furnace, and then calcined under nitrogen protection at a temperature of 300° C. for 2 h, and an aerogel-like substance is formed after the calcination;
[0126] S5: placing the aerogel into a corundum crucible, and introducing a microwave heating device for efficient calcination, wherein the frequency of the microwave calcination is set to 2.45 GHz, the power is set to 2 kW, the microwave calcination temperature is set to 700° C., and the calcination time is 2 h. After the calcination, the decomposition of iron sulfate and aluminum sulfate is completed to obtain a third mixture;
[0127] S6: Grind the third mixture with a ball mill, and conduct a leaching experiment with pure water. The leaching temperature is 80° C., the leaching time is 2 h, and the liquid-to-solid ratio is 3 mL / g. After the leaching is completed, the leaching rates of iron, aluminum, and lithium are calculated.
[0128] Test Case
[0129] The leaching rates of iron, aluminum and lithium in Examples 1-3 and Comparative Examples 1-5 were calculated, and the sintering phenomenon was observed, and the results are shown in Table 1. The leaching rates of iron, aluminum and lithium were calculated from the iron, aluminum and lithium content in the clay lithium ore and the leaching solution.
[0130] Table 1
[0131]
[0132]
[0133] The results show that compared with Comparative Examples 1-5, Examples 1-3 can avoid sintering during the insulation process and leakage caused by excessive clay lithium ore, and can efficiently improve the leaching rate of lithium while reducing the leaching rates of aluminum and iron. The mass ratio of the solvent to the first mixture in Comparative Example 1 is 1:5. Since the solvent formed by glucose and urea has compatibility problems with clay lithium ore, the amount of clay lithium ore added cannot be increased indefinitely. If too much clay lithium ore is added, the solvent cannot completely wrap the clay lithium ore, resulting in leakage of the clay lithium ore. The clay lithium ore added in Comparative Example 1 exceeds the upper limit that the solvent can wrap, resulting in leakage of the clay lithium ore. Comparative Example 2 adopts the traditional sulfuric acid roasting method, and aluminum and iron are also leached in large quantities while leaching lithium, which brings difficulties to the subsequent separation and purification of lithium, and sintering occurs during the insulation process, which makes it difficult to remove the sample from the container, thereby increasing the difficulty of subsequent leaching operations. Compared with Example 1, Comparative Example 3 does not add urea, so it is impossible to effectively form an aerogel-like substance; at the same time, the traditional roasting method is used, which further causes local overheating of the material and reduces the lithium leaching rate. Similarly, compared with Example 1, Comparative Example 4 does not add an effective carbon source and adopts a traditional roasting method, which also causes sintering of the clay lithium ore during the roasting process, reducing the lithium leaching rate. The difference between Comparative Example 5 and Example 1 is that the mass ratio of the carbon source and the foaming agent is changed, that is, the proportion of the foaming agent is reduced, thereby affecting the subsequent bubbling process of the solvent, resulting in partial sintering of the clay lithium ore during the roasting process, and at the same time reducing the number of pores and specific surface area of the aerogel-like substance, thereby affecting the microwave absorption efficiency of the acidification roasting process and the salt decomposition process, thereby reducing the lithium leaching rate.
[0134] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0135] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for extracting lithium from clay lithium ore, characterized in that: include: The carbon source and the foaming agent are mixed and heat-treated to obtain a solvent; Treating the clay lithium ore with acid to obtain a first mixture; mixing the first mixture and the solvent to obtain a second mixture; calcining the second mixture to obtain an aerogel-like substance; The aerogel-like substance is subjected to microwave calcination to obtain a third mixture; The third mixture is subjected to water leaching treatment to obtain a leaching solution and leaching residue.
2. The method according to claim 1, characterized in that The carbon source includes at least one of glucose, sucrose, maltose, fructose and lactose; Optionally, the foaming agent includes at least one of urea, ammonium chloride, melamine, magnesium nitrate, dicyandiamide, and hexamethylenetetramine; Optionally, the mass ratio of the carbon source to the foaming agent is 1:(0.5-1.5).
3. The method according to claim 1, characterized in that The temperature of the heat treatment is 100-130°C; Optionally, the heat treatment time is 8 to 12 minutes.
4. The method according to claim 1, characterized in that: The acid treatment includes mixing the clay lithium ore with sulfuric acid; Optionally, the concentration of the sulfuric acid is 70 to 90 wt %; Optionally, the mass ratio of the sulfuric acid to the clay lithium ore is (1-3):
1.
5. The method according to claim 1, characterized in that The mass ratio of the solvent to the first mixture is 1:(1-4).
6. The method according to claim 1, characterized in that The temperature of the calcination treatment is 200-300°C; Optionally, the calcination treatment time is 0.5 to 3 hours; Optionally, the calcination treatment is performed in an inert atmosphere.
7. The method according to claim 1, characterized in that The power of the microwave roasting treatment is 0.1 to 6 kW; Optionally, the temperature of the microwave roasting treatment is 600-800°C; Optionally, the microwave roasting treatment is performed for 0.5 to 2.5 hours.
8. The method according to claim 1, characterized in that The temperature of the water immersion treatment is 60-100°C; Optionally, the water immersion treatment time is 60 to 150 minutes.
9. The method according to claim 1, characterized in that: The method further comprises: subjecting the leaching solution to lithium precipitation to obtain lithium carbonate.
10. The method according to claim 1, characterized in that The particle size of the clay lithium ore is 80-325 meshes.